Development of the health promoting sports club—national audit tool. (26th August 2022) - Johnson, Stacey; Vuillemin, Anne; Lane, Aoife; Dowd, Kieran; Geidne, Susanna; Kokko, Sami; Donaldson, Alex; Seghers, Jan; Whiting, Stephen; Van Hoye, Aurélie
Abstract: Background: Sports clubs have requested support from national governing authorities to invest in health promotion (HP), by developing policies, guidelines and dedicated funding. This article outlines the development of a national audit tool to review policies development and implementation to support HP in sports clubs. Methods: A five-step process was undertaken by an international project team: (i) a rapid literature review to identify items assessing policies in physical activity, HP and sports, (ii) a thematic analysis to categorize items, (iii) a Delphi method to analyze item relevance, country specificity, reformulation, validation and organization, (iv) face validity through an online survey and in-depth interviews with expert representatives on physical activity and sports and (v) audit tool finalization though project team consensus. Results: Eight sources were reviewed with 269 items identified. Items were coded into 25 categories with 3 broad themes: policies, actors and settings-based approach. The Delphi study extracted and refined 50 items and categorized them into 10 sections. After revisions from 22 surveys and 8 interviews, consensus was reached by the international project team on 41 items categorized into 11 sections: Role of ministry or department; Policies; Communication; Implementation and Dissemination; Evaluation and Measurement methods; Sub-national-level policies; Funding and Coordination; Participative approach; Actors and Stakeholders; National sporting events; Case studies and Implicated stakeholders. Conclusion: To progress HP in the sports club context it is necessary to understand existing national-level policies. This national audit tool will aid in monitoring and assessing national policies for health promoting sports clubs.